2013
DOI: 10.1016/j.msard.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of blood-to-brain transfer rate in multiple sclerosis

Abstract: Blood–brain barrier (BBB) disruption visualized in lesions by MRI is a major biomarker of disease activity in multiple sclerosis (MS). However, in MS, destruction occurs to a variable extent in lesions as well as in gray matter (GM) and in the normal appearing white matter (NAWM). A method to quantify the BBB disruption in lesions as well as in non-lesion areas would be useful for assessment of MS progression and treatments. The objective of this study was to quantify the BBB transfer rate (Ki) in WM lesions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…However, a number of observations suggest caution in interpreting K i as a BBB permeability marker. First, other studies using variations of DCE-MRI have only shown insignificant trends for higher K i values in MS subjects (Silver et al 2001;Lund et al 2013;Taheri et al 2013). Secondly, we reported a correlation between K i , CSF leukocyte count, and matrix metalloprotease 9 (Cramer et al 2015), an enzyme involved in leukocyte infiltration, in MS patients.…”
Section: Introductionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, a number of observations suggest caution in interpreting K i as a BBB permeability marker. First, other studies using variations of DCE-MRI have only shown insignificant trends for higher K i values in MS subjects (Silver et al 2001;Lund et al 2013;Taheri et al 2013). Secondly, we reported a correlation between K i , CSF leukocyte count, and matrix metalloprotease 9 (Cramer et al 2015), an enzyme involved in leukocyte infiltration, in MS patients.…”
Section: Introductionsupporting
confidence: 47%
“…; Taheri et al . ). Secondly, we reported a correlation between K i , CSF leukocyte count, and matrix metalloprotease 9 (Cramer et al .…”
Section: Introductionmentioning
confidence: 97%
“…1C). We determined in each individual the arterial input function (AIF) from the common carotid artery instead of using an average value from the superior sagittal venous sinus to determine tracer concentration in blood (Taheri et al, 2011a, 2011b, 2013; Larsson et al, 2009). Individual AIF measurements are important particularly if the studied population diverges by age as changes in blood volume and flow may affect AIF and the K trans measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to a previous approach limited to measurements of BBB permeability in the white matter (WM) (Taheri et al, 2011a, 2011b, 2013), the current method allows simultaneous measurements of BBB K trans permeability in different grey and WM regions. Additionally, we analyzed CSF biomarkers of BBB breakdown, injury to brain vascular cells including pericytes and endothelial cells, inflammatory response, neuronal injury ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In two more recent studies, the BBB permeability measured as K i was estimated in healthy human subjects using the Patlak method. The first study reported a mean permeability for a conventional MRI contrast agent of 0.013 ml/100 g/min based on measurements on 10 healthy subjects 30 and the second study found an upper limit of normal permeability of 0.03 ml/ 100 g/min 23 based on 20 healthy controls. This is in good agreement with our findings and also show that subtle changes in the BBB permeability can be detected in patients with vascular cognitive impairment and MS patients.…”
Section: Discussionmentioning
confidence: 99%